Preliminary checklist of freshwater fishes of Ulu Paip Eco-Park Forest, Kedah, Peninsular Malaysia - Mohamad Aqmal-Naser,; Amirrudin Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This report is the first on freshwater fishes of Ulu Paip Eco-Park Forest, Kedah, which aims to document the fish species richness in this recreational forest. All species were collected from the main stream, Sungai Karangan, and its unnamed tributaries. In total, 20 species of fishes from 10 families were recorded. Cyprinidae is the most dominant family with six species followed by Danionidae with three species. Other families contribute at least one species each. Most of the species recorded here are commonly found in the northern part of Peninsular Malaysia. Further studies should be expected to record more species and the utilization of various sampling gear such as electro fishing technique would be able to record the true species richness of fishes in this area.